Uncovering readiness factors influencing the Lean Six Sigma pre-implementation phase in the food industry - Azalanzazllay, Nurul Najihah; Abdul Halim Lim, Sarina; Ungku Zainal Abidin, Ungku Fatimah; Anass, Cherrafi (MDPI AG, 2022)
The aim of this study is to identify the readiness factors of Lean Six Sigma (LSS) for the food manufacturing industry. A multi-method qualitative approach was used. Semi-structured interviews were conducted with twelve quality practitioners and three case food companies to identify and explore the LSS readiness factors in the food manufacturing industry. Twenty-eight factors were identified and classified into six LSS readiness factors (RF) in the food manufacturing industry context, namely, management support and leadership, organisational culture readiness, process management, project management, employee involvement, and external relations. This study could benefit managers in the food business as a diagnostic tool to evaluate their readiness to implement LSS prior to investing in the programme. The proposed framework identifies LSS readiness dimensions and their attributes to enable food businesses to conduct readiness level self-assessments, thereby contributing to the successful implementation of LSS in the food manufacturing industry. The determined readiness factors will potentially enable an organisational transformation to be better understood, making the implementation of LSS practices in food businesses more successful and sustainable.